Smooth Muscle-Alpha Actin Inhibits Vascular Smooth Muscle Cell Proliferation and Migration by Inhibiting Rac1 Activity. - Lihua Chen; Allison DeWispelaere; Frank Dastvan; William R A Osborne; Christine Blechner; Sabine Windhorst; Guenter Daum (PLoS ONE, 2016)
Smooth muscle alpha-actin (SMA) is a marker for the contractile, non-proliferative phenotype of adult smooth muscle cells (SMCs). Upon arterial injury, expression of SMA and other structural proteins decreases and SMCs acquire a pro-migratory and proliferative phenotype. To what extent SMA regulates migration and proliferation of SMCs is unclear and putative signaling pathways involved remain to be elucidated. Here, we used lentiviral-mediated gene transfer and siRNA technology to manipulate expression of SMA in carotid mouse SMCs and studied effects of SMA. Overexpression of SMA results in decreased proliferation and migration and blunts serum-induced activation of the small GTPase Rac, but not RhoA. All inhibitory effects of SMA are rescued by expression of a constitutively active Rac1 mutant (V12rac1). Moreover, reduction of SMA expression by siRNA technology results in an increased activation of Rac. Taken together, this study identifies Rac1 as a downstream target for SMA to inhibit SMC proliferation and migration.